Randomized, double-blind, placebo-controlled study of the analgesic effect of intraoperative esmolol for laparoscopic gastroplasty - de Morais, Vinicius Barros Duarte (Sociedade Brasileira para o Desenvolvimento da Pesquisa em Cirurgia, 2020)

(untitled) (Acta Cir Bras)
PURPOSE: To evaluate the analgesic effect of esmolol in patients submitted to laparoscopic gastroplasty. METHODS: Forty patients aged between 18 and 50 years with American Society of Anesthesiologists (ASA) physical status scores of II and III who underwent gastric bypass were allocated to two groups. Group 1 patients received a 0.5-mg/kg bolus of esmolol in 30 mL of saline before induction of anesthesia, followed by an infusion at 15 µg/kg/min until the end of surgery. Group 2 patients received 30 mL of saline as a bolus and then an infusion of saline. Anesthesia included fentanyl (3 µg/kg), propofol (2-4 mg/kg), rocuronium (0.6 mg/kg), and 2% sevoflurane, with remifentanil if necessary. The following parameters were evaluated: pain intensity over 24h, remifentanil consumption, the first analgesic request, morphine consumption, and side effects. RESULTS: Pain intensity was lower in the esmolol group except at T0 (after extubation) and 12h postoperatively. Remifentanil supplementation, recovery time, and postoperative morphine supplementation were lower in the esmolol group. No differences in the time to the first analgesic request or side effects were found between the groups. CONCLUSION: Intraoperative esmolol promotes reductions in pain intensity and the need for analgesic supplementation without adverse effects, thus representing an effective drug for multimodal analgesia in gastroplasty.